Strategy of Increasing Human Resources to Improve the Performance of Village Owned Enterprises in Pulang Pisau Regency - Normand Armando Lampe; Kembara Sopather; Nurlia Eka Damayanti; Jonathan Giovanni; Ani Mahrita; Roby Sambung (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study aims to analyze the existing challenges and potentials and to formulate an effective human resource (HR) development strategy to enhance BUMDes performance. Design/Methodology/Approach – This research adopts a qualitative approach through observation, in-depth interviews, and Focus Group Discussions (FGDs) involving village heads and BUMDes directors as primary respondents. Data were analyzed by comparing the results of a self-perception survey (Likert-scale questionnaire) with qualitative insights derived from interviews and discussions, to identify the convergence and divergence between perceived competence and actual performance in the field. Findings – The study reveals a significant gap between managerial self-perception and real-world implementation. While BUMDes managers perceive themselves as visionary, innovative, and entrepreneurial, their actual operations remain constrained by limited managerial skills, weak governance structures, insufficient digital literacy, and political interference in decision-making. Furthermore, BUMDes units tend to run conventional businesses with minimal innovation and limited collaboration. Despite these barriers, visionary and collaborative leadership—characterized by proactivity, community engagement, and a strong social orientation—emerged as the most influential factor in improving BUMDes performance and sustainability. Implications – This research recommends a comprehensive HR development framework integrating continuous capacity building, field-based technical mentoring, the establishment of clear Standard Operating Procedures (SOPs), transparent financial reporting systems, and strategic collaboration among local governments, universities, and the private sector. Consistent implementation of these strategies is expected to accelerate the transformation of BUMDes in Pulang Pisau Regency into independent, innovative, and competitive rural economic enterprises